The sequence of prenatal growth restraint and postnatal catch‐up growth: normal heart but thicker intima‐media and more pre‐peritoneal fat in late infancy. Issue 3 (25th October 2018) - Sebastiani, G.; García‐Beltran, C.; Pie, S.; Guerra, A.; López‐Bermejo, A.; de Toledo, J. S.; de Zegher, F.; Rosés, F.; Ibáñez, L.
Summary: Background: The sequence of prenatal growth restraint and postnatal catch‐up growth leads to a thicker intima‐media and more pre‐peritoneal fat by age 3–6 years. Objectives: To study whether carotid intima‐media thickness (cIMT) and pre‐peritoneal fat differ already between catch‐up small‐for‐gestational‐age (SGA) infants and appropriate‐for‐gestational‐age (AGA) controls in late infancy (ages 1 and 2 years) and whether such differences – if any – are accompanied by differences in cardiac morphology and function. Methods: Longitudinal assessments included body height and weight; fasting glucose, insulin, Insulin‐like growth factor (IGF‐I), high‐molecular‐weight adiponectin; body composition (by absorptiometry); cIMT, aortic IMT, pre‐peritoneal fat partitioning (by ultrasound); cardiac morphometry and function (by echocardiography) in AGA and SGA infants at birth, at age 1 year ( N  = 87), and again at age 2 years ( N  = 68). Results: Catch‐up SGA infants had already a thicker cIMT than AGA controls at ages 1 and 2 years, and more pre‐peritoneal fat by age 2 years (all p values between <0.01 and <0.0001); all cardiac and endocrine‐metabolic results were similar in AGA and SGA infants at ages 1 and 2 years. Conclusions: From late infancy onwards, catch‐up SGA infants have a thicker cIMT and more pre‐peritoneal fat than AGA controls, but their cardiac morphology and function remain reassuringly similar.